On the composite nature of the holotype of Loxodontomys pikumche Spotorno et al., 1998 (Rodentia, Cricetidae, Sigmodontinae) - Teta, Pablo; Pardiñas, Ulyses F. J.; D’elía, Guillermo (Zootaxa, 2011)
Central Chilean populations of the mouse Loxodontomys Osgood were traditionally (e.g., Pine et al., 1979) included as part of the single species recognized in the genus, L. micropus (Waterhouse). Later, Spotorno et al. (1998) considered that they belong to an up to then undescribed species for which they coined the name L. pikumche. This taxon, with type locality in “... Cajón del Río Maipo, sector Cruz de Piedra (34º 10’ S 69º 58’ W, 2.450 msnm), a 55 km S de la Central Hidroeléctrica de Las Melosas... en la Cordillera de la Región Metropolitana” is characterized by a 2n = 32 (NF = 34) and some subtle morphological differences with L. micropus (that, in turn, has a 2n = 34, NF = 36; Spotorno et al., 1998; Teta et al., 2009). More recently, Novillo et al. (2009) reported the first record of L. pikumche in the Argentinean province of Mendoza and added some putative morphological differences with L. micropus to those previously listed by Spotorno et al. (1998). As discussed by Cañon et al. (2010), the morphological characters documented as differences by Novillo et al. (2009) have some degree of variation within populations of L. micropus s.s. (e.g., zygomatic plate morphology, lateral profile of nasals, development of posterior palate process; see Hershkovitz, 1962; Steppan, 1995) or were based on misinterpretation of some features (e.g., both specimens studied by Novillo et al. [2009] has posteriorly divergent toothrows, and not only that of micropus). Indeed, the distinction of L. pikumche was recently put in interdict by Cañon et al. (2010) on the base of molecular and morphological evidence. These authors remarked that several putative diagnostic characters (e.g., molar root numbers, incisor orientation, shape of upper incisor dentine fissure) vary within and among populations of L. micropus s.s. Further, Cañon et al. (2010) suggested that L. pikumche may be a junior synomyn of L. m. alsus (Thomas, 1919).